Cellular Interplay between Cardiomyocytes and Nonmyocytes in Cardiac Remodeling - Norifumi Takeda; Ichiro Manabe (Hindawi Limited, 2011)
Cardiac hypertrophy entails complex structural remodeling involving rearrangement of muscle fibers, interstitial fibrosis, accumulation of extracellular matrix, and angiogenesis. Many of the processes underlying cardiac remodeling have features in common with chronic inflammatory processes. During these processes, nonmyocytes, such as endothelial cells, fibroblasts, and immune cells, residing in or infiltrating into the myocardial interstitium play active roles. This paper mainly addresses the functional roles of nonmyocytes during cardiac remodeling. In particular, we focus on the communication between cardiomyocytes and nonmyocytes through direct cell-cell interactions and autocrine/paracrine-mediated pathways.